The corrosion behaviour of MAO coated AZ80 magnesium alloy with surface indentation of different sizes. (June 2022) - Jia, Xuejiao; Song, Jiangfeng; Zhao, Libin; Jiang, Bin; Yang, Hong; Zhao, Tiantian; Zhao, Hua; Liu, Qiang; Pan, Fusheng
Highlights: The MAO coating had micro cracks and porous structure with the phase of MgO and Mg2 SiO4 . The corrosion resistance of MAO coating was greatly reduced after impaction. The corrosion products film could temporarily improve the corrosion resistance of specimens after immersion. At the later immersion stage, the corrosion performance of the defected coating deteriorated sharply. The corrosion mechanism of MAO with indentation was clarified. Abstract: In order to investigate the effect of surface indentation size on the corrosion behaviour of MAO coated AZ80 magnesium alloy, the laser confocal microscope, scanning electron microscope, X-ray diffractometer and electrochemical test were carried out to study the corrosion process of MAO coated AZ80 and the coatings damaged with different impact heights. The results display that when MAO coating was damaged with the impact height of 400 mm, the corrosion current density of the specimen increased to 8.0 × 10 −1 μA/cm 2 from 3.2 × 10 −1 μA/cm 2 for MAO without indentation. After immersion for 72 h, the corrosion resistance of the damaged specimens decreased sharply because of the defects on the surface. Moreover, the corrosion mechanism for the coatings with different indentation sizes was clarified.